Existence of Solutions for a p-Kirchhoff-Type Problem with Critical Exponent - Hayat Benchira; M. El Mokhtar Ould El Mokhtar; Atika Matallah (Journal of Mathematics)
In this study, we prove the existence of a positive solution for a p-Kirchhoff-type problem with Sobolev exponent.